Assessing the internalization of the mission. Issue 1 (1st February 2016) - Marimon, Frederic; Mas-Machuca, Marta; Rey, Carlos
Abstract : Purpose: – Many companies have a mission statement that they disseminate through corporate communication to stakeholders and particularly to employees. However, the communication action alone does not ensure that employees take true "ownership" of the mission. Having a mission and internalizing that mission are quite different. The purpose of this paper is to provide a scale to assess the internalization of the mission (IM). Additionally, the authors explore the relationship between IM and organizational alignment. Design/methodology/approach: – Based on previous research on mission internalization, the authors test the conditions necessary for reaching true mission internalization. A first sample of 132 managers from two companies was used for an exploratory analysis: thereafter, a second universal sample of 400 people was used to confirm the scale. Structural Equation Modeling was used to analyze the dimensions deployed in the latent IM construct. This construct has been examined as a second-order factor. A multi-group analysis across these two companies provides nomological validation of the IM scale. Findings: – A scale of 18 items gathered under five dimensions is proposed. Accordingly, the findings are that IM comprises five dimensions: leadership, importance, knowledge, co-workers' engagement and implication. The five dimensions count equally for the IM. Practical implications: – This study provides a useful measure to assess the IM. To achieve a good degree of internalization across employees, the employees must feel that the mission is worthy of engagement and that it is aligned with their personal values. Originality/value: – The paper addresses gaps in the current literature on mission statements regarding the effective implementation of the corporate mission. The results can serve as criteria for managers to obtain better IM for all employees.